De l’encomendero au marchand : charité et évangélisation dans le Pérou colonial, xvie-xviie siècles - Aliocha Maldavsky (Cahiers des Amériques Latines)
In this article the author studies the commitment of the laymen to evangelize the Peruvian indigenous people in the 16th and the 17th centuries, by way of their financial participation and charity. It shows that for the sixteenth-century encomenderos the practice of charity towards Indians contributed to establishing their adherence to Tridentine orthodoxy and to justifying their dominant status in the colonial society. The practice of the same kind of charity by a seventeenth-century merchant reveals that this way of social legitimation was still available and perpetuated, from the point of view of the Spanish laity, the religious distinction between Indians, considered as neophytes, and Spanish descendents, assimilated to catholic devouts.